Tick-borne rickettsial pathogens in naturally infected dogs and dog-associated ticks and their role as sentinels of zoonotic rickettsial diseases in Medellin, Colombia (2019)
ABSTRACT: Tick-borne rickettsial pathogens (TBRP) are important causes of infections in both dogs and humans. Dogs play an important role as a biological host for several tick species and can serve as sentinels for rickettsial infections. Our aim was to determine the presence of TBRP in dogs and in dog-associated ticks and their potential risk to human diseases in Medellin, Colombia. DNA for E. canis (16S rRNA and dsb) and A. platys (groEl) was detected in 17.6% (53/300) and 2.6% (8/300) of dogs, respectively. Antibodies against Ehrlichia spp. 82 (27.3%) and Anaplasma spp. 8 (2.6%) were detected in dogs. Antibody reactivity against both agents were found in 16 dogs (5.3%). Eight dogs showed antibody for Rickettsia spp. with titers that suggest 3 of them had a probable exposure to R. parkeri. Rhipicephalus sanguineus s.l. (178/193) was the main tick in dogs, followed by R. microplus (15/193). The minimum infection rates (MIR) in R. sanguineus were 11.8% for E. canis and 3.4% for A. platys. Our results indicate that E. canis and A. platys are the main TBRP infecting dogs and ticks in Medellin, Colombia. Interestingly, we found serological evidence of exposure in dogs for spotted fever group rickettsiae.